Health-related Quality of Life in Hormone Receptor-Positive Early Breast Cancer: Analyses From the Surveillance, Epidemiology, and End Results Medicare Health Outcomes Survey. (July 2022) - Nabulsi, Nadia A; Naing, Khatija W; Deng, Huiwen; Cueto, Jenilee; Asfaw, Alemseged A; Hubbard, Colin C; Zhou, Jifang; Lee, Inyoung; Mitra, Debanjali; Calip, Gregory S; Law, Ernest H
This study describes health-related quality of life (HRQoL) among older Medicare beneficiaries with hormone receptor-positive (HR+) early breast cancer (eBC). Women aged ≥65 years diagnosed with stage I-III HR+ eBC between 1997 and 2014 using the Surveillance, Epidemiology, and End Results Medicare Health Outcomes Survey Data Resource were included. HRQoL was measured using the Short Form Health Survey including physical/mental component summary (PCS/MCS) scores and subscales. Patient surveys  ≤ 24 months post-diagnosis were matched to non-cancer controls. Mean differences in HRQoL were compared using analysis of covariance. Among 1880 HR+ eBC patients versus 5640 matched non-cancer controls, eBC patients surveyed  ≤ 6 months post-diagnosis (n  =  530) scored lower on component scores (PCS mean difference  =  1.6 [95%CI: 0.6-2.6]; MCS mean difference  =  2.0 [95%CI: 1.0-3.0]) and multiple subscales. Among women surveyed 19 to 24 months post-diagnosis (n  =  402), mean differences in HRQoL were modest (PCS: 1.2 [95%CI: 0.1-2.4]; MCS: −1.5 [95%CI: −2.7 to −0.3]). Most differences in HRQoL following diagnosis of eBC did not indicate statistical significance or minimally important difference, emphasizing that preservation of HRQoL is an important and realistic goal among patients with eBC.